Between workshops, voices and experiences: ESI at the University (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This paper seeks to systematize the experiences of Comprehensive Sexual Education (CSE) workshops developed within the framework of Socio-Educational Practices (SEP) and critical outreach at the Facultad de Filosofia y Letras of the Universidad Nacional de Cuyo. The proposal seeks to answer two main questions: Is it possible to implement CSE in argentine universities? What is its potential for pedagogies? From a situated approach and through participatory action research, we propose to construct possible answers regarding the relationship between CSE and pedagogies in the university setting, paying special attention to the experiences of workshop participants, desire, and the emancipatory horizon that CSE proposes.
Keywords: university; critical outreach; feminist pedagogies; sexual education; experiences